The Scythe Book Mowing Hay, Cutting Weeds, and Harvesting Small Grains with Hand Tools. - Tresemer, David (Stackpole Books, 2021)
The Scythe Book shows how a traditional hand tool can often outperform modern technology for cutting grasses and weeds and harvesting small grains, and provides detailed guidance on fitting the scythe to the individual, care and repair of the blade, principles of movement, and much fascinating lore.